Impact of an oral nutritional supplement on nutritional status in older adults with malnutrition: A randomized controlled trial : Oral Nutritional Supplements Improve Nutritional Status in Malnourished Older Adults. - Jayawardena, Ranil; Wickramawardhane, Prasani (Indonesian Nutrition Association, 2024)
Background: The aging population is expanding at an unprecedented rate, leading to a significant increase in the prevalence of malnutrition among older adults. Oral Nutritional Supplements (ONS) have emerged as a widely accepted strategy to address the nutritional needs of this demographic. Objective: This study aimed to evaluate the impact of an ONS on the nutritional status of malnourished older adults. Methods: This was an open-label, randomized-controlled, parallel-group, single-centered study. Recruitment criteria were age ≥60 years, and mini nutrition assessment-short form (MNA-SF) score ≤11. A total of 50 participants were randomly assigned to the intervention (IG) and control (CG) groups (1:1 ratio). The IG received 200 mL of ONS as a bedtime drink for 12 weeks, while the CG received 200 mL of water. Nutrition status, biochemical analysis, and dietary assessment were performed at the beginning and end of the study. Results: Forty-two participants (IG: n=20, and CG: n=22) completed the study. After 12 weeks, the IG showed a significant improvement in the MNA-SF score (p<0.001) compared to the CG (p=0.118). The IG experienced a substantial increment in the vitamin D level (p=0.002). No significant improvements were found in the serum albumin and haemoglobin levels in either group. The intervention led to significant increases in daily intake of energy (p<0.001), carbohydrate (p=0.013), protein (p<0.001), and fat (p<0.001) in comparison to the control group. Conclusion: Supplementing with an ONS, along with a regular diet, significantly improved nutritional status, some biochemical parameters, and daily intake of energy and macronutrients in older adults with malnutrition.